Pedagogical communication skills of preschool teachers: An analysis of spoken language, behavior and gesture communication, and educational tools in early childhood education - Vu-Thuy, Hoan; Do-Thi, Thuy; Nguyen, Ngoc Thi; Ngo-Thi-Kim, Hoan (International Journal of Innovative Research and Scientific Studies, 2025)
Effective pedagogical communication is an essential skill for preschool educators, as it directly influences children's cognitive, emotional, and social development. Preschool teachers employ various communication methods, including spoken language, behavior, and gesture communication skills, as well as the utilization of educational resources that enhance interactivity and engagement in learning. However, disparities in skill levels exist due to differences in training and institutional support. This study analyzes the present condition and competence of preschool educators in employing pedagogical communication tools, concentrating on three primary skill domains: verbal communication, non-verbal indications, and the utilization of educational tools and toys. A cross-sectional survey was performed with 300 preschool educators and 30 administrators from 10 public preschools in Hanoi and Thai Nguyen, Vietnam. Participants evaluated their communication skills on an 18-item questionnaire employing a five-point Likert scale. Data were examined utilizing SPSS 20.0, employing mean scores, standard deviations, and frequency distributions. Research reveals that preschool educators' skills in communication were assessed at an average level (M = 2.96, SD = 0.50). The highest-rated skill group was the utilization of educational tools and toys (M = 3.15, SD = 0.42), whereas spoken language (M = 2.92, SD = 0.53) and behavior and gesture communication skills (M = 2.81, SD = 0.54) received lower ratings. Improvements are required in utilizing verbal communication to regulate children's interactions and in augmenting non-verbal signals. The research underscores the necessity for specialized training initiatives to enhance educators' communication skills, specifically in non-verbal and interactive verbal methods, to elevate the quality of preschool education.